2007
DOI: 10.1590/s0004-282x2007000200021
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação cognitiva breve de pacientes atendidos em ambulatórios de neurologia geral

Abstract: These results reinforce the need of including cognitive evaluation as a routine part of the neurological examination, independently of the presence of specific complaints in this domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 12 publications
4
29
1
11
Order By: Relevance
“…The BCSB sensitivity in this study was relatively lower than what was found for patients from a neurology outpatient clinic or in the community 4,6,14 . Vittielo et al…”
Section: The Sensitivity and Specificity Of Bcsbcontrasting
confidence: 89%
“…The BCSB sensitivity in this study was relatively lower than what was found for patients from a neurology outpatient clinic or in the community 4,6,14 . Vittielo et al…”
Section: The Sensitivity and Specificity Of Bcsbcontrasting
confidence: 89%
“…From the results of the MMSE it was verifi ed that the average of the total scores was 21.7 points that was achieved in some studies [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the BCSB provides five measures related to memory (incidental, immediate, learning, delayed recall and recognition), language, semantic memory and executive functions 16 .…”
Section: Mini-mental State Examination (Mmse) -mentioning
confidence: 99%